ENTREPRENEURIAL FACTORS AND WORK ENVIRONMENT FACTORS FOR MILLENNIAL WOMEN'S PERFORMANCE - Nerry Kristina; Venny Venny; Veny Vironika; Didi Sundiman (MBIA, 2019)
In this modern era, women are starting to be involved in the millennial generation process today. The purpose of this study is to find out which are the most important given entrepreneurial factors which include innovation; motivation and work environment factors that include convenience and working conditions of women of the millennial generation. The data used is interview data with a qualitative approach. The number of samples is five informants. The results of the study indicate that entrepreneurial variables and environmental factors can have a positive effect on millennial women's performance. These results provide motivation and creativity that can improve women's performance on competitive advantage and a conducive work environment to improve women's performance for the better.